Medication Consumption Patterns and Polypharmacy among Community-Dwelling Elderly in Lomé (Togo) in 2017. (9th January 2020) - Gbeasor-Komlanvi, Fifonsi A.; Zida-Compaore, Wendpouiré I. C.; Dare, Ikpindi H.; Diallo, Aboudoulatif; Darre, Tchin P.; Potchoo, Yao; Belo, Mofou; Ekouevi, Didier K.
Abstract : Background . In the sub-Saharan African, region of the world with a fast growing aging population and where the use of herbal products is very common, there is a paucity of data on medication consumption patterns among elderly people. The objective of this study was to assess the prevalence of polypharmacy and its associated factors among community-dwelling elderly in Lomé, Togo, in 2017. Methods . A cross-sectional study was conducted from March to June 2017 in Lomé, Togo among people aged 60 years and older. The Respondent Driven Sampling method was used to recruit participants. Data on socio-demographic characteristics and medication consumption patterns, including the use of medicinal plants and dietary supplements, were collected using a standardized questionnaire during a face-to-face interview at participants' home. Descriptive and binary logistic regression analyses were performed. Results . A total of 370 participants with median age 65 years, (IQR: 62–71) were enrolled in the study. Almost three elderly in five (57.6%) were multimorbid (had two or more chronic diseases). Conventional drugs (78.4%), medicinal plants (14.3%) and other dietary supplements (9.5%) were used by participants. The prevalence of polypharmacy was 22.7% (95% CI: 18.5–27.3%). Concurrent use of conventional drugs and medicinal plants or other dietary supplements was observed among 17.0% of participants and 67.3% reported self-medication. Multimorbidity (aOR = 4.55; 95% CI: [2.42–8.54]) and female sex (aOR = 1.86; 95% CI: [1.00–3.47]) were associated with polypharmacy. Conclusion . One elderly in five uses five or more medications in Togo. Further studies are needed to assess drug-drug interactions and herb-drug interactions among this population.